1999
DOI: 10.1243/0954411991535103
|View full text |Cite
|
Sign up to set email alerts
|

Puncture resistance and tensile strength of skin simulants

Abstract: This study aims ultimately to quantify the force needed to penetrate human tissue. The results will reduce the subjectivity of expert opinion in stabbing incidents. They will also aid clinicians in assessing the severity of injury and help prevent the unnecessary deaths which can occur when this is not fully appreciated. Tensile tests were performed to identify suitable skin simulants with synthetic chamois and pigskin as candidate materials. Quasi-static penetration experiments were also performed in which a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 11 publications
9
91
0
Order By: Relevance
“…[11]. Comparing our own results to those from the literature in Table 3 we see that the present experimental results are similar to those of [3] and [4], who used instrumented blades, and to those of [7] and [8] who used testing machines at quasi-static speeds. Our results appear to differ significantly only from the work of [6], whose forces appear to be substantially greater than all other authors.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…[11]. Comparing our own results to those from the literature in Table 3 we see that the present experimental results are similar to those of [3] and [4], who used instrumented blades, and to those of [7] and [8] who used testing machines at quasi-static speeds. Our results appear to differ significantly only from the work of [6], whose forces appear to be substantially greater than all other authors.…”
Section: Discussionsupporting
confidence: 87%
“…Typically these studies use customized instrumented knives, where the stab-penetration test is performed by a volunteer holding the blade [3,4,5,6]. An alternative technique, which is used here, is to attach an instrumented blade to a machine which drives the stabbing motion [7,8], offering greater control over a range of test variables. In this study, the data obtained through experimentation has been used to develop a finite element model of stab penetration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu & Yeung (2008) observed a greater stress relaxation in specimens cut perpendicular to the fibre direction and a greater viscoelasticity at higher strains. Similarly Ankersen et al (1999) and Lim et al (2011) observed a clear distinction in material stiffness in tensile tests between the two orthogonal directions. The age of the mammalian surrogate is also a pertinent consideration; the collagen content of skin decreases with age and young skin is typically less protective against large strain trauma than older skin which has a proportionally greater elastic region.…”
Section: Skinmentioning
confidence: 70%
“…Due to its thickness skin is commonly tested in tension (Wu et al, 2003) and under quasistatic loading conditions (e.g. Ankersen et al, 1999;Ní Annaidh et al, 2012), though quasistatic responses may not be simply extrapolated to high strain rates without experimental validation. Lim et al (2011) andGallagher et al (2012) conducted dynamic tensile testing on porcine and human skin tissues respectively using a modified Split Hopkinson Pressure Bar (SHPB).…”
Section: Skinmentioning
confidence: 99%